2005
DOI: 10.1007/s11069-004-2419-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Tsunami Preparedness in Coastal Washington, United States

Abstract: A survey of over 300 residents' and visitors' (non-residents) perceptions of tsunami hazards was carried out along the west coast of Washington State during August and September 2001. The study quantified respondents' preparedness to deal with tsunami hazards. Despite success in disseminating hazard information, levels of preparedness were recorded at low to moderate levels. This finding is discussed in regard to the way in which people interpret hazard information and its implications for the process of adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…Substantial numbers of people choose not to, or are unable to evacuate upon receiving hazard warnings (Lindell and Perry, 1992;Johnston et al, 2005;Lindell et al, 2011;Lindell and Perry, 2012), resulting in a compliance rate much less than 100 %. Earthquake ground shaking is often not interpreted by people as a tsunami warning (Gregg et al, 2006), therefore not all people evacuate the hazard zone.…”
Section: Evacuation Departure Time (Id T + Ep T )mentioning
confidence: 99%
“…Substantial numbers of people choose not to, or are unable to evacuate upon receiving hazard warnings (Lindell and Perry, 1992;Johnston et al, 2005;Lindell et al, 2011;Lindell and Perry, 2012), resulting in a compliance rate much less than 100 %. Earthquake ground shaking is often not interpreted by people as a tsunami warning (Gregg et al, 2006), therefore not all people evacuate the hazard zone.…”
Section: Evacuation Departure Time (Id T + Ep T )mentioning
confidence: 99%
“…In the United States, educational programmes have been effective in raising awareness of tsunamis, but have not been effective in modifying human behaviour. For example, recent surveys of Washington state residents who live along the coast revealed that residents were aware of tsunamis, but were not taking any concrete action to prepare for them (Johnston et al 2005). Hence, there is some social element missing in the existing educational approach to motivate change.…”
Section: (B ) Human Response Simulationsmentioning
confidence: 99%
“…Vulnerability as a science involves examining the combination of physical, social, economic, and political components that influence the degree to which an individual, community, or system is threatened by a particular event, as well as their ability to mitigate these threats and recover if the event was to occur (Cutter 2001(Cutter , 2003Cutter et al 2000;Mileti 1999;Hewitt 1997;Wisner et al 2004). Although definitions and applications of the term vulnerability vary (Cutter 1996;Weichselgartner 2001), common elements within the natural hazard's literature include concepts of exposure, sensitivity, and resilience (Cutter et al 2006;Cutter 2003;Dow 1992;Hewitt 1997;Turner et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although definitions and applications of the term vulnerability vary (Cutter 1996;Weichselgartner 2001), common elements within the natural hazard's literature include concepts of exposure, sensitivity, and resilience (Cutter et al 2006;Cutter 2003;Dow 1992;Hewitt 1997;Turner et al 2003). Exposure is related to hazard proximity and the environmental characteristics of a place, while sensitivity and resilience are characteristics of an individual, group, or socioeconomic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation